Getting the Reformation wrong : correcting some misunderstandings - Payton, James R., 1947- (Downers Grove, Ill. : IVP Academic, 2010)
Most students of history know that Martin Luther nailed his ninety-five theses to the Wittenberg Church door and that John Calvin penned the Institutes of the Christian Religion. However, the Reformation did not unfold in the straightforward, monolithic fashion some may think. It was, in fact, quite a messy affair. Using the most current Reformation scholarship, James R. Payton exposes, challenges and corrects some common misrepresentations of the Reformation. --from publisher description.
Includes bibliographical references and indexes.
Keywords: Reformation; Electronic books